Analysis Of "Si Bulus-Bulus Si Rumbuk-Rumbuk" (1872) By Willem Iskandar: An Ecolinguistics Study - Muhammad Hasyimsyah Batubara; Amrin Saragih; Sumarsih Sumarsih; I Wy. Dirgeyasa; Widya Andayani (EXCELLENCE: Journal of English and English Education, 2025)
The interaction between the Mandailing people and their natural environment is represented in the text Si Bulus-Bulus Si Rumbuk-Rumbuk (1872) by Willem Iskandar, which is examined in this work from an ecolinguistic standpoint. This research uses lexical and discourse analysis to find ecological terminology, metaphors, and tales that represent the Mandailing people's holistic worldview of the 19th Century, which views people, animals, and plants as interrelated. It was also discovered that the Si Bulus-Bulus Si Rumbuk-Rumbuk text had embedded local knowledge values and sustainable cultural practices, such as care for the environment and the proscription of overexploitation. By demonstrating that classic literary works may be a helpful source of ecological information, the study's results advance the field of ecolinguistics. Additionally, by incorporating conventional ecological knowledge into contemporary discourse, this study presents a fresh viewpoint for advancing environmental sustainability. This research affirms the significance of conserving regional languages and cultures to maintain ecological values in the face of global environmental issues by establishing a connection between the past and present.